Numerical analysis of flow over bluff bodies with different shapes - Abir , A M; Chowdhury, P R; Saha, G K (Journal of Naval Architecture and Marine Engineering, 2023)
In this study, Ansys Fluent solver with SIMPLE algorithm and K-Epsilon turbulence model is used to determine the drag forces on bluff bodies with different shapes and arrangements at different Reynolds numbers. In the process, the cross-sectional areas of all the bodies are kept approximately the same to keep the amount of material same for all the cases. First, simulations of the 2D unsteady viscous flow around cylinders of circular and elliptical shapes with the same cross-sectional area are performed at Reynolds number 1000. In the case of elliptical cylinder, two different orientations are used, namely: major axis along the flow (horizontal orientation) and major axis perpendicular to the flow (vertical orientation) for aspect ratio of 0.8. The horizontally oriented elliptical cylinder shows the least drag compared to the circular and vertically oriented elliptical cylinders. The vertically oriented elliptical cylinder shows the maximum drag because of the large projected area and early flow separation from the cylinder. Later, the drag coefficients of two circular cylinders of the same diameter in tandem arrangement are investigated at inlet speeds of 2.5, 5, 7.5, and 10.5 knots considering L/D ratios of 2.0, 2.5, and 3.0, where L is the center-to-center distance and D is the diameter of the cylinders. For the upstream(first) cylinder, the flow separation from the cylinder is delayed as the speed increases, and the wake becomes narrower. Consequently, the drag coefficient for the first cylinder decreases with increase in speed. As the speed increases, the disturbance on the downstream(second) cylinder increases with respect to the first cylinder, and hence the drag coefficient increases. Journal of Naval Architecture and Marine Engineering, 20(3), 1–10